Cerebral cortical activity after withdrawal of life‐sustaining measures in critically ill patients. Issue 12 (23rd July 2022) - Gofton, Teneille E.; Norton, Loretta; Laforge, Geoffrey; Gibson, Raechelle; Debicki, Derek; Althenayan, Eyad; Scales, Nathan; Beinum, Amanda Van; Hornby, Laura; Shemie, Sam; Dhanani, Sonny; Slessarev, Marat
Abstract: Establishing when cerebral cortical activity stops relative to circulatory arrest during the dying process will enhance trust in donation after circulatory determination of death. We used continuous electroencephalography and arterial blood pressure monitoring prior to withdrawal of life sustaining measures and for 30 min following circulatory arrest to explore the temporal relationship between cessation of cerebral cortical activity and circulatory arrest. Qualitative and quantitative EEG analyses were completed. Among 140 screened patients, 52 were eligible, 15 were enrolled, 11 completed the full study, and 8 (3 female, median age 68 years) were included in the analysis. Across participants, EEG activity stopped at a median of 78 (Q1 = −387, Q3 = 111) seconds before circulatory arrest. Following withdrawal of life sustaining measures there was a progressive reduction in electroencephalographic amplitude ( p  = .002), spectral power ( p  = .008), and coherence ( p  = .003). Prospective recording of cerebral cortical activity in imminently dying patients is feasible. Our results from this small cohort suggest that cerebral cortical activity does not persist after circulatory arrest. Confirmation of these findings in a larger multicenter study are needed to help promote stakeholder trust in donation after circulatory determination of death. Abstract : This prospective observational cohort study estimated the temporal relationship between cessation of brain cortical electrical activity and circulatory arrest after withdrawal of life sustaining measures in critically ill adults.